2002
DOI: 10.1152/ajplung.00434.2001
|View full text |Cite
|
Sign up to set email alerts
|

Combined SP-A-bleomycin effect on cytokines by THP-1 cells: impact of surfactant lipids on this effect

Abstract: ) plays a role in host defense and inflammation in the lung. In the present study, we investigated the hypothesis that SP-A is involved in bleomycin-induced pulmonary fibrosis. We studied the effects of human SP-A on bleomycin-induced cytokine production and mRNA expression in THP-1 macrophage-like cells and obtained the following results. 1) Bleomycin-treated THP-1 cells increased tumor necrosis factor (TNF)-␣, interleukin (IL)-8, and IL-1␤ production in dose-and time-dependent patterns, as we have observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…21 A substantial amount of evidence accrued from in vitro and in vivo studies using animals or patients has shown that bleomycin upregulates expression of TNF-a, IL-1b and TGF-b pro-inflammatory proteins. 22,23 These cytokines are produced by endothelial cells, alveolar macrophages, lymphocytes, neutrophils and fibroblasts. The role of these cytokines in inflammation, edema formation, fibrosis and tissue remodeling has been well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…21 A substantial amount of evidence accrued from in vitro and in vivo studies using animals or patients has shown that bleomycin upregulates expression of TNF-a, IL-1b and TGF-b pro-inflammatory proteins. 22,23 These cytokines are produced by endothelial cells, alveolar macrophages, lymphocytes, neutrophils and fibroblasts. The role of these cytokines in inflammation, edema formation, fibrosis and tissue remodeling has been well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…SP-A was purified by butanol extraction from the bronchoalveolar lavage (BAL) fluid of alveolar proteinosis patients (13) as described previously (20). The purified protein was examined by two-dimensional gel electrophoresis and silver staining and was found to be Ͼ99% pure.…”
Section: Methodsmentioning
confidence: 99%
“…SP-A was purified (16) from the BAL fluid obtained from a patient with AP (AP BAL hSP-A) as described previously (19). The concentration of SP-A was determined using the Micro BCA Protein Assay (Pierce, Rockford, IL) using RNase A as a standard, and the purity of the SP-A preparation was verified by 2-D-PAGE followed by silver staining.…”
Section: Purification Of Sp-a From Human Balmentioning
confidence: 99%